Mental models and the potential for crop intensification in coastal Bangladesh: How do farmers’ perceptions reflect proposed agricultural development pathways? - Shahrin, Sumona; Krupnik, Timothy J.; Aravindakshan, Sreejith; Groot, Jeroen (Cereal Systems Initiative for South Asia, 2020)
The expanded use of surface water for irrigation, intensified farm management, and double cropping have been highlighted by the Government of Bangladesh as policy priorities and development imperatives in the coastal region. A deltaic country, Bangladesh has a dense network of interconnected rivers and over 230 tributaries flowing into the Bay of Bengal. Most farmers cultivate rice during the summer monsoon. In the subsequent winter season that is characterized by low amounts of rainfall, many farmers do not irrigate despite available surface water resources in naturally flowing canal systems. Rather, they tend to fallow their fields or grow pulses without intensive management practices. Use of available water resources for irrigation, intensified farm management, and double cropping are relatively rare. The reasons for this ‘ironic’ situation are complex. They involve challenges with soil and water salinity, lack of infrastructure and market integration, and farmers’ generally low investment capacity and aversion to risk, among others. Most studies in the coastal region have focused on addressing these issues from a biophysical or agronomic standpoint, or by using econometric approaches to examine farmers’ interest in intensified crop management and the use of irrigation. Considering agronomic management, there are many approaches that have been deemed as technologically feasible. Less information is however available on how different kinds of farmers perceive and approach these complex issues. Similarly, the relevance for policy and development initiatives in coastal Bangladesh is relatively under-researched. Therefore, the objectives of this study were to analyze farmers’ perceptions of their predominant farming systems and explore corresponding constraints and perceptions of the use of surface water as a means to intensify farm management.